A genetic epidemiology study of congenital adrenal hyperplasia in Italy. Issue 2 (17th October 2017) - Gialluisi, A.; Menabò, S.; Baldazzi, L.; Casula, L.; Meloni, A.; Farci, M. C.; Mariotti, S.; Balestrino, L.; Ortolano, R.; Murru, S.; Carcassi, C.; Loche, S.; et al.
Abstract : Congenital adrenal hyperplasia due to 21‐hydroxylase deficiency (21OHD‐CAH) is an autosomal recessive disorder affecting steroidogenesis, due to mutations in CYP21A2 (6p21.3). 21OHD‐CAH neonatal screening is based on 17‐hydroxyprogesterone (17OHP) serum levels, showing high type I error rate and low sensitivity to mild CAH forms. Here, we used an epidemiological approach, which estimates the allelic frequency ( q ) of an autosomal recessive disorder using the proportion of homozygous patients, the mutational spectrum and the inbreeding coefficient in a sample of affected individuals. We applied this approach to 2 independent Italian cohorts of patients with both clinical and molecular diagnosis of 21OHD‐CAH from mainland Italy ( N = 240) and Sardinia ( N = 53). We inferred q estimates of 2.87% and 1.83%, corresponding to a prevalence of 1/1214 and 1/2986, respectively. CYP21A2 mutational spectra were quite discrepant between the 2 cohorts, with V281L representing 74% of all the mutations detected in Sardinia vs 37% in mainland Italy. These findings provide an updated fine‐grained picture of 21OHD‐CAH genetic epidemiology in Italy and suggest the need for a screening approach suitable to the detection of the largest number of clinically significant forms of CAH. Abstract :